2023
DOI: 10.1111/ele.14242
|View full text |Cite
|
Sign up to set email alerts
|

Will a large complex system be productive?

Abstract: While the relationship between food web complexity and stability has been well documented, how complexity affects productivity remains elusive. In this study, we combine food web theory and a data set of 149 aquatic food webs to investigate the effect of complexity (i.e. species richness, connectance, and average interaction strength) on ecosystem productivity. We find that more complex ecosystems tend to be more productive, although different facets of complexity have contrasting effects. A higher species ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
(119 reference statements)
0
3
0
Order By: Relevance
“…Interactions among species are thus a key component of biodiversity, and biodiversity itself is the result of complex biotic interactions that are structured in species networks. In some case, it has also been found that EFs can change with changing the species interaction network (Nie et al., 2023), and this without any change in the species richness (Morrien et al., 2017). This result emphasises that assessing species interactions should be central when identifying and quantifying EFs (Poisot et al., 2013).…”
Section: From Biodiversity To Species Interaction Networkmentioning
confidence: 99%
“…Interactions among species are thus a key component of biodiversity, and biodiversity itself is the result of complex biotic interactions that are structured in species networks. In some case, it has also been found that EFs can change with changing the species interaction network (Nie et al., 2023), and this without any change in the species richness (Morrien et al., 2017). This result emphasises that assessing species interactions should be central when identifying and quantifying EFs (Poisot et al., 2013).…”
Section: From Biodiversity To Species Interaction Networkmentioning
confidence: 99%
“…And because the effects of introductions cascade through interaction networks, it is often difficult to predict whether they will reinforce or undermine the integrity of a given ecosystem [11,18,19]. Thus, attempting to artificially increase complexity can have unintended consequences [13,20,21] and entail trade-offs with other desirable system features, like resilience, robustness, or productivity [16,[22][23][24].…”
Section: More Complexity Is Not Always Bettermentioning
confidence: 99%
“…Network complexity can be characterized by species richness, connectance and average interaction strength. 35,36 It is generally believed that stability increases as the number of links increases as complex communities can prevent the populations from over-explosive growth and species invasion. 37 Furthermore, weak interaction strengths may enhance species coexistence and increase temporal community stability.…”
Section: Introductionmentioning
confidence: 99%